Orthokeratinized odontogenic cyst - critical appraisal of a distinct entity - Aditi Byatnal; Jayalakshmi Natarajan; Venkadasalapathy Narayanaswamy; Raghu Radhakrishnan (Universidade Estadual de Campinas, 2015)
The orthokeratinized odontogenic cyst (OOC) is a rare developmental jaw cyst. Recognition of OOC as a unique entity has long been due, yet its inexplicable radiographic presentation resembling dentigerous cyst, histological likeness to odontogenic keratocyst (OKC) and inconsistent cytokeratin expression profiles overlapping with both as well as with the epidermis, makes it rather confounding. Diagnosis of OOC is important as the pathologic behavior, clinical outcome and the surgical management of OOC is disparate. This is the report of a case of OOC in relation to an impacted mandibular third molar and critical review of this entity with an emphasis on its biologic characteristics is highlighted.